PENGARUH KAPABILITAS SUMBERDAYA DAN TOP MANAGEMENT SUPPORT TERHADAP INOVASI DAN MODERASI KETIDAKPASTIAN LINGKUNGAN TERHADAP RISIKO INOVASI - Endah Rahayu Lestari; Rizky Luthfian Ramadhan Silalahi; Dhiksa Noer Annasa (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Innovation is a complex process and uncertain. Therefore, important aspects of innovation success must be considered. Launching new products is not easy, expensive, and risky because new product development requires costs, and the product must have more value than other similar products. The availability of resources can increase a company's capacity to support innovation. Product development or innovation cannot be carried out well without management commitment or Top Management Support (TMS). The purpose of this research is to empirically examine the effect of resources capability, and Top Management Support on innovation and its implications for innovation risks both directly and moderated by environmental uncertainty. The study using structural modeling and data analysis employing Partial Least Square (PLS). The results reveal that resource capability and top management support have a positive effect on innovation, and the higher environmental uncertainty increases the risk of innovation.